Determinan Tingkat Pengangguran Terdidik Studi Kasus: 6 Negara OECD 2018-2022 - Sindy Aliya Putri, Cantika; Didu, Saharuddin; Desmawan, Deris (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2025)
This study analyzes the effects of government spending on education, tertiary enrollment, economic growth, and wages on educated unemployment in six OECD countries from 2018 to 2022. Data from the World Bank and OECD were analyzed using panel data regression (Fixed Effect Model) in EViews-12. Results show all variables jointly affect educated unemployment significantly, with R² of 91.88%. Partially, education spending and tertiary enrollment have positive significant effects, wages have a negative significant effect, and economic growth is insignificant. These findings underscore the importance of aligning education policies with labor market needs to enhance educated labor absorption and reduce mismatch.